Global capitalism theory and the emergence of transnational elites - William I. Robinson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The class and social structure of developing nations has undergone profound transformation in recent decades as each nation has incorporated into an increasingly integrated global production and financial system. National elites have experienced a new fractionation. Emergent transnationally-oriented elites grounded in globalized circuits of accumulation compete with older nationally-oriented elites grounded in more protected and often state-guided national and regional circuits. This essay focuses on structural analysis of the distinction between these two fractions of the elite and the implications for development. I suggest that nationally-oriented elites are often dependent on the social reproduction of at least a portion of the popular and working classes for the reproduction of their own status, and therefore on local development processes however so defined whereas transnationally-oriented elites are less dependent on such local social reproduction. The shift in dominant power relations from nationally- to transnationally-oriented elites is reflected in a concomitant shift to a discourse from one that defines development as national industrialization and expanded consumption to one that defines it in terms of global market integration.
Keywords: F01; F54; F59; P16; 330; Elites; development; globalization; transnational; capitalism; crisis; Elite; Wirtschaftliche Macht; Verhalten; Globalisierung; Kapitalismus; Krisentheorie; Entwicklungstheorie; Entwicklungsländer